Family Communication Model in Establishing Understanding of Media Literacy - Mas Amah; Ferly Tanggu Hana (Universitas Muhammadiyah Yogyakarta, 2019)
The research aims to find the communication behavior of Posyandu's (Indonesian maternal and child health service) attendants in establishing understanding of media literacy, the challenges they should face, including the solutios, as well as the family communication model. The research is vital since, in addition to a notion that effective media literacy started from a family, the attendants have been educated with various topics by various institution, including media literacy, making them suitable to be the representation of informative family and society’s fine example. The research is a qualitative reseach using a case-study as the method. The informants are Posyandu’s attendants, their family members, public figures, and the leader of KPID NTT that are determined with a purposive sampling. The data colections method used are interview, observation, and documentation while the data analysis are data reduction, data display, drawing and verifying conclusion, analyzing the data, and making summary. The finding demonstrate that Posyandu’s attendant restrict family television time limit and internet use to raise understanding toward media literacy. Inconsistency in applying the rules and parents’s difficulty in using the internet outright are the challenges that are dealth with. The attendants redirect the family members to assist them in doing chores and limit funding for purchasing internet data to tackle the problem.